Income and Feasibility of Rice Farming (Oryza sativa L.) in Pauh Duo District South Solok Regency - Fauzi, Dian (JURNAL PANGAN, 2023)
Rice is one of the food crops in the agricultural sector, providing sustenance in the form of rice consumed by the majority of the population. Additionally, it serves as a crucial source of income for farmers. This study aimed to analyze the characteristics of farmers, analyze the income and feasibility of lowland rice farming in Pauh Duo District, South Solok Regency. Proportional random sampling was used to select respondents, with a total of 45 participants drawn from a population of 4032 individuals. Income and feasibility analyses were conducted as the primary tools for examination. The results showed that the average income obtained by rice farmers was Rp13,843750.00/ha/MT, with the average cost was Rp7,270,669.79/ha/MT. Consequently, the average income accrued was Rp8,760,453.65/ha/MT. The R/C analysis demonstrated the feasibility of lowland rice farming in the Pauh Duo District, South Solok Regency, with an obtained R/C value of 1.90. This implied that every Rp1 incurred as a cost by the farmer generated an income of 1.90.